161k views
19 votes
What are the steps for solving
6x-1=-x+9

User Soothran
by
6.1k points

2 Answers

4 votes

Answer:

x = 10 / 7

Explanation:

6x - 1 = -x + 9

Add 1 to both sides of the equation.

6x - 1 = -x + 9

6x - 1 + 1 = -x + 9 + 1

Simplify

Add the numbers

6x - 1 + 1 = -x + 9 + 1

6x = -x + 9 + 1

Add the numbers

6x = -x + 9 + 1

6x = -x + 10

Add x to both sides of the equation.

6x = -x + 10

6x + x = -x + 10 + x

Simplify

Combine like terms

6x + x = -x + 10 + x

7x = -x + 10 + x

Combine like terms

7x = -x + 10 + x

7x = 10

Divide both sides of the equation by the same term

7x = 10

7x/7 = 10/7

Simplify

Cancel terms that are in both the numerator and denominator.

7x/7 = 10/7

x = 10/7

Solution

x = 10/7

I hope this helps have a great day!!!

6 votes

Answer:

x=10/7

Let's solve your equation step-by-step

6x−1=−x+9

Step 1: Add x to both sides

6x−1+x=−x+9+x

7x−1=9

Step 2: Add 1 to both sides

7x−1+1=9+1

7x=10

Step 3: Divide both sides by 7

7x/7=10/7

x=10/7

User Berniey
by
5.1k points